PENGARUH CITRA MEREK, DESAIN PRODUK, DAN CELEBRITY ENDORSEMENT TERHADAP NIAT BELI ULANG - Miftahul Anam; Prihatini Budi Astuti (Universitas Ahmad Dahlan, 2022)
This study aims to determine the effect of brand image, product design, and celebrity endorsement on the repurchase intention of consumers of soccer shoes. The object of this research is the consumer of soccer shoes in Kebumen Regency. The sampling method of this study was an accidental sampling technique with 100 respondents. The data analysis technique was the multiple linear regression analysis with the SPSS program. The results showed that brand image has no significant effect on repurchase intention. Meanwhile, product design and celebrity endorsement have a positive effect on repurchase intention.